Dynamic Monitoring of Kidney Injury Over 3 Days in Intensive Care Unit in Patient with Sepsis and Its Association with ICU Mortality - Aqeel; Mustafa, Ghulam; Khan, Muhammad Kamran; Sabeen, Amber; Naeem, Nabiha; Tahir, Zuha (Indus Journal of Bioscience Research, 2025)
Introduction: Acute Kidney Injury (AKI) is a common complication in septic patients, significantly contributing to ICU mortality. The dynamic changes in kidney function over the initial days of ICU admission remain a crucial factor in determining patient outcomes. Objective: This study aimed to assess the association between changes in kidney injury markers and ICU mortality in septic patients. Additionally, it evaluated the predictive value of dynamic biomarker fluctuations over three days and the potential benefits of early biomarker-based interventions. Methodology: A retrospective observational study was performed at Aga Khan University Hospital (Karachi). A total of 229 out of 772 ICU admissions were selected based on predefined inclusion criteria. Patients were categorized into normal, improved, and deteriorated groups based on AKI progression from day 1 to day 3. Key biomarkers such as serum creatinine and urine output were analyzed. Statistical analyses, including correlation and multivariate regression, were performed to assess mortality predictors. Results: The deteriorated group had significantly higher APACHE II (p = 0.02) and SOFA scores (p < 0.001). CKD (G4-G5) was more prevalent in this group (55.9%, p < 0.001). ICU mortality was significantly higher in the deteriorated group (26.5%, p = 0.021), with a steep decline in survival by day 56 (45.2% vs. 62.9% in non-deteriorated patients). Multivariate analysis identified worsening AKI as an independent predictor of mortality. Conclusion: Dynamic changes in kidney injury markers over the first three days of ICU admission are strong predictors of mortality in septic patients. Early identification of deteriorating kidney function and timely interventions can potentially improve survival rates.